Archaeozoology of Southwest Asia and adjacent areas XIII : proceedings of the Thirteenth International Symposium, University of Cyprus, Nicosia, Cyprus, June 7-10, 2017 - Daujat, Julie; Hadjikoumis, Angelos; Berthon, Rémi; Chahoud, Jwana; Kassianidou, Vasiliki; Vigne, Jean-Denis (Archaeobiology, 2021)
"Southwest Asia is at the epicenter of zooarchaeological research on pivotal changes in human history such as animal domestication and the emergence of social complexity. This volume continues the long tradition of the ASWA conference series in publishing new research results in the zooarchaeology of southwest Asia and adjacent areas. The book is organized in three thematic areas. The first presents new methodological tools and approaches in the study of animal remains exemplified through studies on domestication, butchery practices, microdebris, intrasite contextual comparisons and age-at-death recording. Besides offering interesting insights into our past, these methodological developments enable higher resolution for future research. The second section focuses on the subsistence economies of prehistoric and early complex societies and provides new insights into how animal management developed in southwest Asia. The third section includes intriguing new research results on the roles of animals in the symbolic world of ancient societies, such as the meaning of insect figures at Göbekli Tepe, animal cults in Egypt, feasting in Iron Age Oman, and the ornithological interpretation of Byzantine mosaics"--